PEMBANGUNAN JEMBATAN DALAM RANGKA MEMBUKA KETERISOLIRAN DAERAH DI KABUPATEN INDRAGIRI HILIR (DITINJAU DARI ASPEK PERENCANAAN, PELAKSANAAN DAN PENGAWASAN) - Agung Zulyadain (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Development in the field of construction, one of which is the improvement of roads and bridges, which are infrastructure to support various developments, even infrastructure in the development of the region as a whole. Indragiri Hilir Regency is one of several regions that have natural potential that can be used as an increase in the regional economy with the widest stretch of coconut that has ever existed, thus, if supported by a smooth transportation flow, it will facilitate the production and distribution process